Extracorporeal membrane oxygenation support for hypertrophic cardiomyopathy in an infant of a diabetic mother. (6th March 2017) - Udine, Michelle L.; Romp, Robb L.; Jackson, Kimberly W.
Abstract: Infants of diabetic mothers are at risk for transient hypertrophic cardiomyopathy. These infants are typically asymptomatic, but may develop signs of poor cardiac output from left ventricular outflow tract obstruction. This case illustrates the successful use of extracorporeal membrane oxygenation to support cardiac output in an infant of a diabetic mother with outflow tract obstruction until hypertrophy improved.